Optimizing Free Writing Using Notion As A Digital Space For Student Creative Expression - Gayuh Elga Pamungkas; Khoir Umam (Universitas Pendidikan Ganesha, 2026)
This study investigated the optimization of free writing activities using Notion as a digital space to support students’ creative expression in English writing. The research was conducted due to the limited engagement and low confidence commonly found in conventional writing practices. The purpose of this study was to examine how Notion facilitated students’ freedom of expression, writing fluency, and motivation. A qualitative descriptive method was employed involving undergraduate students who participated in structured free writing activities using Notion over several sessions. Data were collected through students’ written products, observations, and reflective responses. The findings indicated that the use of Notion encouraged students to write more freely, reduced anxiety toward writing tasks, and enhanced creativity through flexible layouts and digital organization. In conclusion, Notion proved to be an effective digital platform for optimizing free writing and fostering creative expression in EFL classrooms.